Effect of early low-dose hydrocortisone on survival without bronchopulmonary dysplasia in extremely preterm infants (PREMILOC): a double-blind, placebo-controlled, multicentre, randomised trial. Issue 10030 (30th April 2016) - Baud, Olivier; Maury, Laure; Lebail, Florence; Ramful, Duksha; El Moussawi, Fatima; Nicaise, Claire; Zupan-Simunek, Véronique; Coursol, Anne; Beuchée, Alain; Bolot, Pascal; Andrini, Pierre; Mohamed, Damir; et al.
Summary: Background: Bronchopulmonary dysplasia, a major complication of extreme prematurity, has few treatment options. Postnatal steroid use is controversial, but low-dose hydrocortisone might prevent the harmful effects of inflammation on the developing lung. In this study, we aimed to assess whether low-dose hydrocortisone improved survival without bronchopulmonary dysplasia in extremely preterm infants. Methods: In this double-blind, placebo-controlled, randomised trial done at 21 French tertiary-care neonatal intensive care units (NICUs), we randomly assigned (1:1), via a secure study website, extremely preterm infants inborn (born in a maternity ward at the same site as the NICU) at less than 28 weeks of gestation to receive either intravenous low-dose hydrocortisone or placebo during the first 10 postnatal days. Infants randomly assigned to the hydrocortisone group received 1 mg/kg of hydrocortisone hemisuccinate per day divided into two doses per day for 7 days, followed by one dose of 0·5 mg/kg per day for 3 days. Randomisation was stratified by gestational age and all infants were enrolled by 24 h after birth. Study investigators, parents, and patients were masked to treatment allocation. The primary outcome was survival without bronchopulmonary dysplasia at 36 weeks of postmenstrual age. We used a sequential analytical design, based on intention to treat, to avoid prolonging the trial after either efficacy or futility had been established. This trial is registered withClinicalTrial.gov, numberNCT00623740 . Findings: 1072 neonates were screened between May 25, 2008, and Jan 31, 2014, of which 523 were randomly assigned (256 hydrocortisone, 267 placebo). 255 infants on hydrocortisone and 266 on placebo were included in analyses after parents withdrew consent for one child in each group. Of the 255 infants assigned to hydrocortisone, 153 (60%) survived without bronchopulmonary dysplasia, compared with 136 (51%) of 266 infants assigned to placebo (odds ratio [OR] adjusted for gestational age group and interim analyses 1·48, 95% CI 1·02–2·16, p=0·04). The number of patients needed to treat to gain one bronchopulmonary dysplasia-free survival was 12 (95% CI 6–200). Sepsis rate was not significantly different in the study population as a whole, but subgroup analyses showed a higher rate only in infants born at 24–25 weeks gestational age who were treated with hydrocortisone (30 [40%] of 83 vs 21 [23%] of 90 infants; sub-hazard ratio 1·87, 95% CI 1·09–3·21, p=0·02). Other potential adverse events, including notably gastrointestinal perforation, did not differ significantly between groups. Interpretation: In extremely preterm infants, the rate of survival without bronchopulmonary dysplasia at 36 weeks of postmenstrual age was significantly increased by prophylactic low-dose hydrocortisone. This strategy, based on a physiological rationale, could lead to substantial improvements in the management of the most premature neonates. Funding: Assistance Publique-Hôpitaux de Paris.